20 International online survey of 1162 individuals with functional neurological disorder: demographics, symptom comorbidities, self- management strategies, and illness beliefs. Issue 8 (20th July 2020) - Butler, Matthew; Seynaeve, Mathieu; Pick, Susannah; Rucker, James; Nicholson, Timothy
Abstract : Aims: Functional neurological disorder (FND) is common and often severe. It is poorly understood, and there have been no international large-scale studies of self- management and illness beliefs in FND. We created a patient questionnaire to assess FND demographics, symptom comorbidity, self-management strategies (particularly in relation to prohibited substances), views on novel treatments, and illness beliefs. Methods: The questionnaire was shared open access over a three-week period. Participants were recruited internationally through social media and patient groups. RESULTS: In total, 1162 respondents from 16 countries took the survey. Of these, 98% reported a formal diagnosis of FND from a consultant neurologist or other suitably trained clinician. Females constituted 86% of respondents, with an average age of 41.7 years (SD=12.50). Mean symptom duration was 7.69 years (SD=9.37) and average time from diagnosis was 2.24 years (SD=3.35), indicating a diagnostic lag of over 5 years. Symptom comorbidity was very high, with respondents reporting current: seizures (50%), gait disturbance (76%), loss of balance (77%), tremors (61%), muscle jerks/spasms (65%), altered sensations (79%), speech difficulties (65%), memory problems (80%), fatigue (93%), and headache (70%). Current psychiatric comorbidities – depression (43%), anxiety (51%), panic (20%), and PTSD (22%) - were also common. Illness beliefs varied, with respondents agreeing most strongly that FND is a combination of physical and stress/trauma-related factors. Respondents rated FND as having a severe effect on their life, with little control felt over their symptoms. Respondents had received a wide range of medical interventions, and many had tried alternative treatments. Prohibited substances such as cannabis, ketamine, and psychedelics had been used by 15% of respondents, with the majority experiencing no or minimal physical (90%) and psychological (95%) sequelae. Many respondents reported that they would be willing to try medically supervised psychedelic therapy if it was found to be safe and effective. Conclusions: This large international online survey of FND patients indicated a striking co-occurrence of multiple symptoms. As expected, respondents reported that FND severely impacted on their lives, and many had lived with symptoms, which are not well managed by current medical therapies, for years. There was interest in novel putative treatments, such as medically supervised psychedelic therapies, which indicates a strong need to investigate alternative treatments for this poorly served patient group.